A Componential Analysis of the Semantic Field “Beat” - Дзидоликене, Вита (Kalbotyra, 1988)
The verb “beat”, the nucleus of this field, is made up of three fundamental semantic components: (1) intense purposeful movement, (2) usage of a blowcarrying instrument, (3) contact between instrument and object (subject). The three fundamental components occur in different meanings of the verb “beat” in combination with differential semantic components. The parsing of the verb “beat” into semantic components may serve as a means for picking out the verbs and phraseologisms of this field. The nucleus of the field “beat” is made up of the dominant “beat” and the verbs most closely related to it: pummel, pound, thrash, buffet, baste, belabour.